Peristiwa Penyaliban Yesus Ditinjau dari Perspektif Sejarah dan Teologi Yohanes - Daniel Lindung Adiatma (IMMANUEL: Jurnal Teologi dan Pendidikan Kristen, 2022)
The event of the crucifixion of Jesus Christ has caused controversy for some circles. For Christians, this event marks a major change in human life in obtaining eternal life. For non-religious historians, these events are ordinary events that do not have any meaning in history. But they admit that the crucifixion of Jesus is considered a major event for mankind. His example influences mankind to become civilized human beings. In addition, there are some people who do not believe that the crucifixion of Jesus is a factual event and can be trusted. The assumption is, Jesus was released from the punishment of the cross and went to other areas to preach the gospel. Although the latter opinion is not supported by valid data and has received opposition from Christian historians and theologians, it is still believed by several groups of people. This study seeks to assess historical facts about the crucifixion of Jesus Christ from a historical and theological perspective so that the validity of the events of Jesus' death cannot be doubted and increases Christian belief in the event not only at the faith level, but also at the academic level. The author will present historical data from leading historians and literary analysis of the Gospel of John 11:1-12:36 to find the historical factuality of the crucifixion of Jesus and the theological meaning behind the event. In his study, the author will compare the opinions of historians who lived close to the time of Jesus and John as narrators and witnesses of the death of Jesus. Finally, readers can believe in the factuality and history of Jesus' crucifixion which is interpreted as a glory for the Son of God and has an impact on the lives of believers.AbstrakPeristiwa penyaliban Yesus Kristus telah menimbulkan kontroversi bagi beberapa kalangan. Bagi orang Kristen, peristiwa tersebut menandai perubahan besar dalam kehidupan manusia dalam memperoleh kehidupan kekal. Bagi sejarahwan non keagamaan, peristiwa tersebut merupakan peristiwa biasa yang tidak memiliki makna apapun dalam sejarah. Tetapi mereka mengakui bahwa peristiwa penyaliban Yesus dianggap sebagai peristiwa besar bagi umat manusia. Keteladan-Nya memberikan pengaruh bagi umat manusia agar menjadi manusia yang beradap. Selain itu, ada beberapa kalangan yang tidak meyakini peristiwa penyaliban Yesus sebagai peristiwa yang faktual dan dapat dipercayai kebenarannya. Asumsinya, Yesus dilepaskan dari hukuman salib dan pergi ke daerah lainnya untuk memberitakan injil. Meskipun pendapat terakhir tersebut tidak didukung dengan data-data yang valid dan memperoleh pertentangan dari sejarahwan dan teolog Kristen, namun pendapat tersebut masih diyakini oleh beberapa kelompok orang. Penelitian ini berusaha untuk menilai fakta sejarah tentang penyaliban Yesus Kristus dari perspektif sejarah dan teologi sehingga validitas peristiwa kematian Yesus tidak dapat diragukan dan meningkatkan keyakinan orang Kristen terhadap peristiwa itu bukan saja pada tingkat iman, melainkan juga pada tingkat akademis. Penulis akan memaparkan data-data sejarah dari sejarahwan terkemuka dan analisis sastra Injil Yohanes 11:1-12:36 untuk menemukan faktualitas sejarah penyaliban Yesus dan makna teologis di balik peristiwa tersebut. Dalam kajiannya, penulis akan membadingkan pendapat sejarawan yang hidup dekat dengan masa Yesus dan Yohanes sebagai narator dan saksi peristiwa kematian Yesus. Akhirnya, pembaca dapat meyakini faktualitas dan historitas penyaliban Yesus yang dimaknai sebagai kemuliaan bagi Anak Allah dan berdampak pada kehidupan orang percaya.